2022
DOI: 10.1101/2022.05.19.22275214
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Antibody levels following vaccination against SARS-CoV-2: associations with post-vaccination infection and risk factors

Abstract: SARS-CoV-2 antibody levels can be used to assess humoral immune responses following SARS-CoV-2 infection or vaccination, and may predict risk of future infection. From cross-sectional antibody testing of 9,361 individuals from TwinsUK and ALSPAC UK population-based longitudinal studies (jointly in April-May 2021, and TwinsUK only in November 2021-January 2022), we tested associations between antibody levels following vaccination and: (1) SARS-CoV-2 infection following vaccination(s); (2) health, socio-demograp… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 72 publications
2
2
0
Order By: Relevance
“…Our findings are consistent with previous immunology studies that reported higher antibody levels following BNT–BNT versus AZ–AZ 16-18 , including studies in dialysis and kidney transplant recipients 6,19 . Higher effectiveness for BNT–BNT versus AZ–AZ has also been reported during the Delta wave in study populations not restricted to individuals with kidney disease 20,21 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings are consistent with previous immunology studies that reported higher antibody levels following BNT–BNT versus AZ–AZ 16-18 , including studies in dialysis and kidney transplant recipients 6,19 . Higher effectiveness for BNT–BNT versus AZ–AZ has also been reported during the Delta wave in study populations not restricted to individuals with kidney disease 20,21 .…”
Section: Discussionsupporting
confidence: 92%
“…The administration of BNT as a third dose appeared to compensate for the discrepancies in protection between AZ- and BNT-primed individuals. This finding is consistent with observational and clinical studies of third-dose immunogenicity in healthy adults 16,24 and individuals with kidney disease 7,9,25 , as well as vaccine effectiveness data from the general population 26 . One previous study explored short-term vaccine effectiveness of BNT as a third dose following AZ or BNT priming among haemodialysis recipients, reporting increased protection against Omicron infection for boosted compared with unboosted individuals and no significant differences according to primary vaccine group 27 .…”
Section: Discussionsupporting
confidence: 88%
“…The optimal timing of booster vaccination remains unclear, with some advocating for annual COVID-19 vaccines [41]. Given the existing evidence demonstrating that SARS-CoV-2 antibody levels are associated with COVID-19 risk [12][13][14] and disease COVID-19 severity [15][16][17], antibody models may play a role in informing booster vaccination strategies. Our 11 month data indicates that antibody levels peak within 1 month, and then decline up to approximately 10 months.…”
Section: Discussionmentioning
confidence: 99%
“…Given evidence of waning SARS-CoV-2 humoral immune responses after vaccination, booster vaccinations have been implemented in many jurisdictions; however, the optimal timing for boosters remains unclear. There is growing evidence that SARS-CoV-2 antibody levels provide a measure of COVID-19 risk [12][13][14] and COVID-19 severity [15][16][17], a relationship that has been shown to be present even within the Omicron era [18]. Thus, antibody levels may inform decisions regarding the optimal timing of a booster vaccination.…”
Section: Introductionmentioning
confidence: 99%